Forest Management in the Interface: Wildlife - Jim Parkhurst; Martha C. Monroe (EDIS)
Revised! FOR-182, a 7-page illustrated fact sheet by Jim Parkhurst and Martha Monroe, highlights key wildlife management issues in interface forests and provides background information on potential conflicts. Includes references. Published by the UF School of Forest Resources and Conservation, October 2008.